2018
DOI: 10.1002/jcop.22097
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of unaccompanied women experiencing homelessness

Abstract: This study explored strengths, barriers, and role of social networks among unaccompanied women experiencing homelessness. Twenty women from two local shelters participated in semistructured, face‐to‐face interviews. A constant comparative analysis revealed 4 themes: support as a coping mechanism, loss of support as a path to homelessness, support as a drain, and support as a way to give. Almost universally, women experienced considerable barriers to housing, including physical health, mental health, substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(83 reference statements)
1
4
0
2
Order By: Relevance
“…The lack of a family and affective ties makes Maria transform the shelter into her “home” by generating new networks that allow her social ties to be re-affiliated, thus reducing isolation and the feeling of loneliness. This experience is consistent with the findings of Groton and Radey [ 38 ], who mention the loss of primary social networks such as the family and violence in the relationships within one’s social networks as key elements leading to homelessness. They also conclude that building new social networks is a powerful coping mechanism and that willingness to help peers generates a strong sense of wellbeing.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of a family and affective ties makes Maria transform the shelter into her “home” by generating new networks that allow her social ties to be re-affiliated, thus reducing isolation and the feeling of loneliness. This experience is consistent with the findings of Groton and Radey [ 38 ], who mention the loss of primary social networks such as the family and violence in the relationships within one’s social networks as key elements leading to homelessness. They also conclude that building new social networks is a powerful coping mechanism and that willingness to help peers generates a strong sense of wellbeing.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between social connections and health is well established, in that our social relationships affect our mental and physical health and mortality [ 47 ]. Research by Groton and Radey [ 48 ] with homeless women, identified that social support was integral to people who were homeless, enabling them to cope with their situation whilst, conversely, a loss of support contributed to or prolonged their homelessness. As such, perhaps having a mobile phone and internet access should be seen as an essential rather than a luxury item for those who are homeless.…”
Section: Discussionmentioning
confidence: 99%
“…Observou-se que em todos os estudos havia pelo menos uma mulher responsável por seu(s) filho(s), e seis deles estipularam como critério de participação ser mulher e mãe em situação de rua. (BENBOW et al, 2011;GROTON;RADEN, 2018;GULTEKIN et al, 2015;HUEY, 2016;KIRKMAN et al, 2015;BRETAS, 2015;SOUZA et al, 2016;WHITZMAN, 2010). É alarmante a expressividade dos relatos de abuso físico e sexual perpetrados por homens na vida dessas mulheres, presentes ao longo de toda a sua trajetória de vida, seja testemunhando atos de violência conjugal contra a sua mãe, seja sofrendo violência na infância e na fase adulta (CRAWFORD et al, 2011;SCHMIDT et al, 2015;SOUZA et al, 2016).…”
Section: Resultsunclassified
“…Muitas mulheres relataram vivenciar situações de preconceito por raça, gênero e por situarem-se nas ruas, além de violências psicológicas, verbais e negligências (BISCOTTO et al, 2016;COSTA et al, 2015;CRAWFORD et al, 2011;GROTON;RADEN, 2018 VUILLERMOZ, 2017;WHITZMAN, 2010).…”
Section: Resultsunclassified